High altitude exposure and ischemic stroke: A literature review - Ortíz Prado, Esteban; Dunn, Jeff F. (Revista de la Facultad de Ciencias Médicas (Quito), 2017)
<span style="color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Despite our understanding of stroke, the risk factors involved and its treatment and prevention, stroke remains the second leading cause of death among humans worldwide. Several risk factors have been associated with higher incidences of stroke, such as hypertension or diabetes, while non-traditional risk factors such as vitamin D deficiency or cardiac valvular thickness have recently been identified. The potential role of hypoxia or high altitude exposure as a risk factor has not been clearly established. This review includes the relationship between acute and chronic high altitude exposure and the possible development of ischemic stroke in high altitude populations. Several risk factors are identified in high altitude dwellers such as polycythemia, increased platelet adhesiveness and greater risk to develop vascular thrombosis. Other conditions such as dehydration, extreme cold and immobilization might lead to increased risk of ischemic stroke in newcomers. Taking into account the limited number of studies, it is argued that high altitude and chronic hypoxia may be risk factors for the development of ischemic stroke. The altitude associated with higher prevalence of ischemic stroke is not clear, but it appears that there is increased risk above 3000m.